Virtual Communication to Every Valorant Online Game Player in Developing Game Strategy - Dadan Saputra; Hera Sawitri (International Journal of Education, Information Technology, and Others, 2023)
With the rapid development of internet technology, online games are also growing rapidly. Online games offer a new nuance where social interactions with other people become more intense through cyberspace. With the internet, it triggers a form of communication in the media, namely virtual communication. Virtual communication that occurs between online game players is very important because this virtual communication can be in the form of strategic planning or providing information about opponents to the team. The problem discussed in this study is how virtual communication processes and patterns occur in every Valorant online game player in developing game strategies. This research uses a type of descriptive qualitative research with data sources, namely the results of interviews with informants and other supporting data. The data that has been collected was analyzed using descriptive qualitative data analysis of Miles and Huberman's interactive model, namely data reduction, data presentation, drawing conclusions and verification, while the validity of the data was checked using source triangulation. Furthermore, the results of the research data were analyzed and linked to the Computer Mediated Communication Theory to find out how the processes and patterns of virtual communication are carried out by players in the online game Valorant. The results of this study indicate that, 1) the virtual communication process that occurs in every Valorant online game player is in the form of conveying a message from an idea or idea from a team member which is expressed through the voicechat and chatbox/text chat features, then absorbed by other players, resulting in various reciprocity or feedback and lead to a flow of communication. 2) There are three communication patterns that are more dominantly used by every online game player, namely primary, secondary, and circular communication patterns. 3) there are virtual communication barriers in the online game Valorant such as signals, and also in terms of hardware.